Evaluation of Hope in patients with cancer in hospital of Shahid gazie’s Tabrize. - Baljani, esfandyar; Arax, Marlin; Mohammad Alizadeh, Sakeenah (Advances in Nursing & Midwifery, 2012)
Abstract Background and Aim Materials and methods Results : 51.3% of participants were female. 51% of patients had leukemia and 71/7% were receiving chemotherapy. 30.4% were promising and 53.1% of patients had moderate hopes and none of them were not disappointed. Between patient gender, cancer type, education level, marital status, type of treatment, treatment duration and type of cancer associated with hope scores were not statistically significant correlation, but correlation were found with financial status, living arrangement, level of activity, physical energy, problem with sleep, health care delivery and ostracism from family members Discussion: Among the factors associated with cancer patients hope, caregivers and family behavior, level of activity, employment status, problem with sleep, and ostracism from family members are agents correlated with hope scores. Nurses and family members of patients with promotion of conditions associated with these variables can help to maintain hope in these patients. Keywords: Cancer- Hope- Coping